ANALISIS EFEKTIVITAS HARGA DAN BIAYA DALAM KAMPANYE PERGURUAN TINGGI KESEHATAN DENGAN MENGGUNAKAN INFLUENCER KESEHATAN TIKTOK - Jariyah, Mufidatul; Yaqin, Nurul; Wardhana, Bayu; Dewi, Shanti Allena (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
Influencers play an important role in today's digital market because they can directly influence, invite and promote a program. In terms of health priorities, posts on influencer social media accounts must be accurate and provide information about the content presented, because it influences the audience's decision making and actions. This research analyzed data from the social media site TikTok regarding professional influencers in the health industry and conducted an in-depth study of the content engagement formula on each creator's account. The research method used in this research uses descriptive qualitative methods using secondary data. This research uses several influencers, which will then illustrate how to calculate the Return of Investment. The results of this study show that ROI estimates of over 100% confirm that investing in health promotion initiatives with professional health influencers yields significant and substantial returns. ROI in social media marketing, with special emphasis on intangible outcomes such as brand recognition, customer engagement/relationships and eWOM. Practical implications of the findings Health professional influencers on social media TikTok generate different responses from other social media platforms. As for the benefits of the research, it is hoped that this research can show the efficacy of efficient social media influencers on the TikTok platform as a cost-effective social media health promotion techniqu